2021
DOI: 10.1016/j.isci.2021.103273
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of prefoldins and their implication in cancer

Abstract: Summary Prefoldins (PFDNs) are evolutionary conserved co-chaperones, initially discovered in archaea but universally present in eukaryotes. PFDNs are prevalently organized into hetero-hexameric complexes. Although they have been overlooked since their discovery and their functions remain elusive, several reports indicate they act as co-chaperones escorting misfolded or non-native proteins to group II chaperonins. Unlike the eukaryotic PFDNs which interact with cytoskeletal components, the archaeal P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 208 publications
(279 reference statements)
0
14
0
Order By: Relevance
“…Table 1 summarizes the identified interactors with different prefoldin subunits. A recent review described links between interactors of prefoldin subunits and the progression of cancer ( Liang et al, 2020 ; Herranz-Montoya et al, 2021 ). The sections below focus on the involvement of prefoldin subunits in transcription, protein aggregation, and degradation.…”
Section: Non-canonical Functions Of the Prefoldin Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the identified interactors with different prefoldin subunits. A recent review described links between interactors of prefoldin subunits and the progression of cancer ( Liang et al, 2020 ; Herranz-Montoya et al, 2021 ). The sections below focus on the involvement of prefoldin subunits in transcription, protein aggregation, and degradation.…”
Section: Non-canonical Functions Of the Prefoldin Complexmentioning
confidence: 99%
“…Cancer refers to a group of disorders that are caused by the uncontrolled division of cells that may start in every organ of the body and, in severe cases, spread to other organs ( Hausman, 2019 ). Several studies reported the contribution of the prefoldin complex and its subunits to the onset and progression of some cancers ( Table 2 ) ( Liang et al, 2020 ; Herranz-Montoya et al, 2021 ). Higher prefoldin expression was observed in cancer cell lines compared with non-cancerous cells ( Boudiaf-Benmammar et al, 2013 ).…”
Section: Implications Of Prefoldin In Pathological Conditionsmentioning
confidence: 99%
“…Ribosome (Khatter et al, 2015) Ribosome biogenesis (Ameismeier et al, 2018;Bohnsack and Bohnsack, 2019;Liang et al, 2020) Translation initiation (Jackson et al, 2010) Translation elongation (Antonellis and Green, 2008;Dever et al, 2018) Translation termination (Hellen, 2018) Ribosomal quality control (Brandman and Hegde, 2016;Duttler et al, 2013;Joazeiro, 2019) Chaperones and folding enzymes General (Brehme et al, 2014;Jayaraj et al, 2020;Shemesh et al, 2021) HSP70 system (Bracher and Verghese, 2015;Brocchieri et al, 2008;Kampinga and Craig, 2010;Mayer and Gierasch, 2019;Rosenzweig et al, 2019) HSP90 system (Pearl, 2016;Schopf et al, 2017;Taipale et al, 2014) TRiC/CCT system (Gestaut et al, 2019;Herranz-Montoya et al, 2021;Mukherjee et al, 2010;Tian and Cowan, 2013;Willardson and Howlett, 2007) sHSP (Boncoraglio et al, 2012;Garrido et al, 2012;Reinle et al, 2022) PDI (Galligan and Petersen, 2012) PPIase (Pemberton and Kay, 2005)…”
Section: Protein Synthesismentioning
confidence: 99%
“…Animal and yeast models show that prefoldin-like proteins are regulators of cell survival and proliferation in response to environmental and nutrient stress [1]. Prefoldin-like proteins were identified in several independent studies in animals and yeast.…”
mentioning
confidence: 99%
“…URI is unique among prefoldin and prefoldin-like proteins in that it is a larger protein. In addition to its involvement in several cellular functions related to its role as a cochaperone, either as part of the PFDL complex or as an independent subunit, its role as a signaling protein has also been described [1]. In yeast, URI/Bud27 is involved in transcription indirectly by assembling the three nuclear RNA polymerases in the cytoplasm [11] and directly by modulating their transcriptional activity in close association with the chromatin remodeler RSC [12][13][14][15].…”
mentioning
confidence: 99%